Synergistic Utility of Brain Natriuretic Peptide and Left Ventricular Global Longitudinal Strain in Asymptomatic Patients With Significant Primary Mitral Regurgitation and Preserved Systolic Function Undergoing Mitral Valve Surgery. (July 2016) - Alashi, Alaa; Mentias, Amgad; Patel, Krishna; Gillinov, A. Marc; Sabik, Joseph F.; Popović, Zoran B.; Mihaljevic, Tomislav; Suri, Rakesh M.; Rodriguez, L. Leonardo; Svensson, Lars G.; Griffin, Brian P.; Desai, Milind Y.
Abstract : Background—: In asymptomatic patients with ≥3+ mitral regurgitation and preserved left ventricular (LV) ejection fraction who underwent mitral valve surgery, we sought to discover whether baseline LV global longitudinal strain (LV-GLS) and brain natriuretic peptide provided incremental prognostic utility. Methods and Results—: Four hundred and forty-eight asymptomatic patients (61±12 years and 69% men) with ≥3+ primary mitral regurgitation and preserved left ventricular ejection fraction, who underwent mitral valve surgery (92% repair) at our center between 2005 and 2008, were studied. Baseline clinical and echocardiographic data (including LV-GLS using Velocity Vector Imaging, Siemens, PA) were recorded. The Society of Thoracic Surgeons score was calculated. The primary outcome was death. Mean Society of Thoracic Surgeons score, left ventricular ejection fraction, mitral effective regurgitant orifice, indexed LV end-diastolic volume, and right ventricular systolic pressure were 4±1%, 62±3%, 0.55±0.2 cm 2, 58±13 cc/m 2, and 37±15 mm Hg, respectively. Forty-five percent of patients had flail. Median log-transformed BNP and LV-GLS were 4.04 (absolute brain natriuretic peptide: 60 pg/dL) and −20.7%. At 7.7±2 years, death occurred in 41 patients (9%; 0% at 30 days). On Cox analysis, a higher Society of Thoracic Surgeons score (hazard ratio 1.55), higher baseline right ventricular systolic pressure (hazard ratio 1.11), more abnormal LV-GLS (hazard ratio 1.17), and higher median log-transformed BNP (hazard ratio 2.26) were associated with worse longer-term survival (all P <0.01). Addition of LV-GLS and median log-transformed BNP to a clinical model (Society of Thoracic Surgeons score and baseline right ventricular systolic pressure) provided incremental prognostic utility (χ 2 for longer-term mortality increased from 31–47 to 61; P <0.001). Conclusions—: In asymptomatic patients with significant primary mitral regurgitation and preserved left ventricular ejection fraction who underwent mitral valve surgery, brain natriuretic peptide and LV-GLS provided synergistic risk stratification, independent of established factors. Abstract : Supplemental Digital Content is available in the text.